INNOVATION OF INSTITUTIONS AND PROHIBITION RE-REVIEW OUTER-ISLAND MARKETING OF COWS TO INCREASE VALUE ADDED OF BEEF CATTLE - Krova M. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
Nowadays, beef cattle marketing in production center namely Kupang Regency tends to lead to unequally depletion of farmers’ value added. The farmers value added was an important thing to motivate them in using technology to increase productivity and sustainability for all actors in the beef cattle supply chain. Research objectives were to analyse the farmers’ value added and to stimulate policy needed, therefore it will increase the farmers’ value added. The research was a case study in the beef cattle supply chain. Key informant persons were determined by applying snow ball sampling from downstream to upstream. Number of key informants depends on saturation information and model validation result include their behaviour understanding. Data collected were numeric, written, and mental model. Data, then, were analysed by applying the value added and system dynamic modelling with Vensim software application. The result showed that the farmers have the smallest value added average of IDR 4,284,277.15 annually with profit margin IDR8,676,500.40 per year and the value added ratio was 8.49 %. Middlemen have the highest value added IDR 60,529,650.00 per year and profit margin IDR61,705,650.00 per year, and the value added nisb was 14.98 % decrease, followed by abbatoir traders, and the middlemen coordinator. The highest value added ratio gained by the abbatoir marketters was 21.5.%. The result of policy simmulation decreases the difference of cattle price between the middlemen and the farmers, and equalize the price of cow and bull. The result really can increase the farmers’ value added. Further, innovation of the farmers’ cooperative institution to increase the farmers’ bargaining power and to re-review the prohibition of outer-island marketing cows in order to equalize the price of bull and cow.